Cowpea (Vigna unguiculata [L.] Walp.) germplasm collection in southern Italy and preliminary evaluation - Laghetti, G.; Padulosi, S.; Hammer, K.; Cifarelli, S.; Perrino, P. (1990)
In Italy cowpeas are grown primarily for green pod production. During 1986-88, 3 collecting missions covering the regions of Campania, Basilicata, Apulia and Calabria were mounted by the Germplasm Institute, Bari. A total of 177 seed samples were collected (147 of cowpeas and 30 of asparagus beans (V. unguiculata subsp. sesquipedalis)) from 120 sites. Severe genetic erosion was noted, particularly in Basilicata and Calabria, due to farmers no longer growing the crop or using seed from commerical sources which replace local landraces. The accessions were characterized for 23 quantitative and qualitative characters. Most accessions had a subglobose leaf shape (82%), indeterminate habit (82%) and glabrousness (98%). Variability was high for seed shape and colour, days to first flower (50-140 days), days to first ripe pod (64-152 days), pod length (64-710 mm) and 100-seed weight (6-30 g).